Human chorionic gonadotropin–positive seminoma patients: A registry compiled by the global germ cell tumor collaborative group (G3). (June 2020) - Seidel, Christoph; Daugaard, Gedske; Nestler, Tim; Tryakin, Alexey; Fedyanin, Mikhail; Fankhauser, Christian; Hermanns, Thomas; Aparicio, Jorge; Heinzelbecker, Julia; Paffenholz, Pia; Heidenreich, Axel; De Giorgi, Ugo; et al.
Abstract: Background: The prognostic role of human chorionic gonadotropin (hCG) and lactate dehydrogenase (LDH) serum levels in seminoma patients remains uncertain. This observational study evaluates the prognostic impact of tumour marker levels, and other clinicopathological findings, in hCG-positive seminoma patients. Methods: Seminoma patients with serum hCG levels above normal at first diagnosis were eligible for recruitment. Statistical analysis, including multivariate regression, was performed to identify risk factors. Primary end-points were overall survival (OS) and recurrence-free survival (RFS). Results: We recruited 1031 hCG-positive patients (stage I: n = 586; stage II + III: n = 427) diagnosed between 1981 and 2018. In metastatic disease, LDH levels ≥3 above upper normal limit (UNL) pre- ( n = 109) or post-orchiectomy ( n = 73) and patients aged ≥40 years ( n = 187) were associated with poor prognosis: 5-year OS rates of 84% (LDH ≥3 UNL pre-orchiectomy) versus 92% (<3 UNL pre-orchiectomy) (hazard ratio [HR]: 3.155, [95% confidence interval CI: 1.28–7.75], P = 0.012), 82% (≥3 UNL post-orchiectomy) versus 92% (<3 UNL post-orchiectomy) (HR: 6.877, [95% CI: 1.61–29.34]; P = 0.009) and 86% (≥40 years) versus 91% (<40 years) (HR: 6.870, [95% CI: 1.45–13.37], P = 0.009), respectively. A subset of patients with hCG levels ≥2000 IU/l pre-orchiectomy ( n = 17) exhibited a poor prognosis, with 5-year OS rates of 73% (≥2000 IU/l) versus 94% (<2000 IU/l) (HR: 3.936, [95% CI: 1.02–12.61], P = 0.047). Conclusions: Age and LDH levels are significantly associated with poor prognosis in hCG-positive seminoma patients. A small number of patients, with levels of hCG ≥2000 IU/l, may represent a separate prognostic subgroup associated with impaired survival rates. Highlights: Human chorionic gonadotropin (hCG) levels correlate with clinical disease burden. Exceptionally high levels of hCG were detected in a small subgroup of patients with seminoma. Four percent of patients with advanced disease had hCG levels ≥2000 IU/l associated with a poor prognosis. Lactate dehydrogenase levels ≥3 above upper normal limit inversely correlate with outcome.